THE INFLUENCE OF THE LEARNING TOGETHER LEARNING MODEL ON LEARNING OUTCOMES THEMATICS OF CLASS IV STUDENTS BADDOKA STATE ELEMENTARY SCHOOL - Gifa Nurfauziah; Nurhayati Selvi; Musbaing (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This study aims to determine. 1) description of the application of the Learning Together model to thematic learning for fourth grade students 2) description of thematic learning outcomes for fourth grade students 3) the effect of the Learning Together learning model on thematic learning outcomes for fourth grade students of SD Negeri Baddoka. The type of experimental research and the object of this research were fourth grade students at SD Negeri Baddoka. Data collection techniques in this study are observation, testing and documentation. The data in this study were analyzed using descriptive and inferential statistical analysis in the form of normality, homogeneity and hypothesis tests. The results of this study indicate that (1) the application of the learning together learning model in thematic learning of fourth grade students at SD Negeri Baddoka increased based on the observations of teachers and students (2) The learning outcomes of fourth grade students at SD Negeri Baddoka increased based on the results of pretest and posttest scores obtained the pretest average was 66.33 while the posttest score was 79.77. (3) Learning Together learning model influences the thematic learning outcomes of fourth grade students at SD Negeri Baddoka. Based on the results of the t test which shows that the Sig.(2-talled) value of 0.001 is smaller than 0.05, which means there is an influence